Análise do processo de lixamento com lixas de óxido de alumínio - Fonseca, Mariane Alves [UNESP] (2012)
The wood products, such as lumber, panels, veneer and other products made from wood require finishing. Most often these are dependent on the sanding process. The purpose of this procedure is to make surface corrections generated at the time of production of parts by irregularities of the timber. Thereby facilitating the application of varnishes, paints and other products to improve the quality of products of the wood industry. The sanding process is influenced by factors such as specific cutting pressure, particle size of sandpaper, sanding time, cutting speed, among others. In this paper will be studied the influence of particle size of aluminum oxide sandpaper, analyzing the variability of the wear of abrasive grains, being applied in Eucalyptus sp and Pinus elliottii, held in plan sanding. The analysis will be performed, having as parameter, cutting force and power input during the procedure. Roughness will also be analyzed to see if there was a significant influence in these different conditions